Local order drives the metallic state in PEDOT:PSS. Issue 29 (5th July 2016) - Stadler, Philipp; Farka, Dominik; Coskun, Halime; Głowacki, Eric D.; Yumusak, Cigdem; Uiberlacker, Lisa M.; Hild, Sabine; Leonat, Lucia N.; Scharber, Markus C.; Klapetek, Petr; Menon, Reghu; Sariciftci, N. Serdar
Abstract : Ordering of PEDOT:PSS by self-organization results in a metallic transition described by weak localization. Abstract : Weak localization describes a metallic system, where due to the presence of disorder the electrical transport is governed by inelastic electron relaxation. Therefore the theory defines a threshold of spatial and of energetic disorder, at which a metal–insulator transition takes place. To achieve a metallic state in an inherently disordered system such as a conductive polymer, one has to overcome the threshold of localization. In this work we show that the effective suppression of disorder is possible in solution-processible poly(3, 4-ethylenedioxythiophene)–poly(styrene sulfonate). We grow polymer films under optimized conditions allowing self-organization in solution. Interestingly, we find the requisite threshold, at which the system becomes finally metallic. We characterize the transition using a complementary morphology and magneto-electrical transport study and find coherent electron interactions, which emerge as soon as local order exceeds the macromolecular dimensions. These insights can be used for discrete improvement in the electrical performance, in particular for tailoring conductive polymers to alternative metal-like conductors.